2008
DOI: 10.1016/j.seizure.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Smoking reduces serum levels of lamotrigine

Abstract: The influence of smoking on lamotrigine (LTG) serum levels in 44 patients with epilepsy treated with LTG in monotherapy was examined. Fifteen patients were smokers (range: three cigarettes per month -- three packages per day) and 29 were non-smokers. Analyzing 204 samples, smokers had a significantly lower serum level-to-dose ratio than non-smokers (0.0657mmolmg/l (smokers) vs. 0.0785mmolmg/l (non-smokers)) (p=0.0014). Analyzing only male patients, the same relationship with an almost equally high level of sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…We confirmed previously a demonstrated effect of smoking on LTG metabolism . Compared with non‐smokers, LTG clearance was 34% (95% CI 14.7, 59.0%) higher in patients who smoked.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We confirmed previously a demonstrated effect of smoking on LTG metabolism . Compared with non‐smokers, LTG clearance was 34% (95% CI 14.7, 59.0%) higher in patients who smoked.…”
Section: Discussionsupporting
confidence: 90%
“…Previous published studies showed that various factors such as weight , age , pregnancy , smoking , blood urea nitrogen : serum creatinine ratio , race , LTG daily dose [31], oral contraceptives and use of concurrent AEDs influence LTG plasma concentrations. Additionally, genetic polymorphisms in genes encoding drug‐metabolizing enzymes UGT1A4 , UGT2B7 and ABCB1 transporter [21] were also suggested to contribute to the IIV of LTG CL.…”
Section: Discussionmentioning
confidence: 99%
“…21 We also evaluated the effect of smoking on LTG. Only 2 of 21 women were smokers, 1 in group B and 1 in group C. Individually, the mean clearance of LTG in smokers was relatively high, which could provide some support to the notion that smoking reduces the serum levels of LTG.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, lamotrigine (LTG) is an AED widely prescribed in association both with first and/or second generation AEDs, which favors the possible occurrence of drug interactions, since its metabolism is known to be influenced by different AEDs (Reinsberger, Dorn, Krämer, 2008;Johannessen, Landmark, 2010). Regardless of the LTG linear pharmacokinetics, its plasma concentration values show high inter-individual variability, as commonly seen in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the LTG linear pharmacokinetics, its plasma concentration values show high inter-individual variability, as commonly seen in clinical practice. In addition to factors related to pharmacotherapy, there are other clinical, physiological, pathological and even demographic factors influencing the pharmacokinetic of LTG (Reinsberger, Dorn, Krämer, 2008;Patsalos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%